Profile of total protein, albumin, globulin and albumin globulin ratio in bulls - Irfan, Ida Zahidah; Esfandiari, A; Choliq, C (Indonesian Journal of Animal and Veterinary Sciences, 2014)
Determination of serum total protein concentration and main fractions (albumin and globulin) can be used as an important diagnostic tool in clinical biochemistry. Several factors can affect the concentration of total protein, albumin, globulin and albumin globulin ratio (A/G). The aim of this study is to obtain serum protein profiles, albumin, globulin and A/G ratio based on breed, age and BCS (body condition score). Blood samples from 160 bulls were collected. Blood chemistry were analyzed  by photometer principle using a commercial kit. There were significant (P<0.001) breed variation on total protein,  albumin, globulin and albumin globulin ratio. Significant age differences were observed on total protein and albumin concentration (P<0.001), while globulin concentration and A/G ratio were also significant (P<0.05). Amongs groups of BCS, significant difference was verified only in the albumin concentration (P<0.05).  The concentration of total proteins, albumins and globulins in the serum of the bulls are higher than standard values for cattle, while A/G ratio is lower. Key Words: Serum Protein Profiles, Bulls, Breed, Age, Body Condition Score